2016
DOI: 10.1556/0806.44.2016.035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of kernel carotenoids in novel maize genotypes possessing rare allele of β-carotene hydroxylase gene

Abstract: Carotenoids are important micronutrients required by humans for growth and development. Yellow maize among cereals possesses sufficient carotenoids, and thus, it is important to genetically dissect such traits for proper utilization in breeding programme. Twenty-one maize hybrids generated using novel inbreds with rare allele of β-carotene hydroxylase (crtRB1) that enhances kernel β-carotene, were evaluated at two diverse maize growing locations. Lutein, zeaxanthin and β-cryptoxanthin were positively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
6
16
0
1
Order By: Relevance
“…The observed significant GCA and SCA effects for grain yield and other agronomic traits in our study indicated the importance of both additive and non-additive gene effects in the inheritance of these traits [32]. Conversely, the significant GCA but non-significant SCA effects for provitamin A and most carotenoids indicated the predominance of additive gene effects in their inheritance, consistent with the results reported in other studies involving maize inbred lines [26,28,30,49,50]. This, however, contradicts with the results of [27,29] who reported the presence of additive and non-additive gene effects in the inheritance of Provitamin A while [31] reported the preponderance of non-additive gene effects in the inheritance of provitamin A and other carotenoids.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed significant GCA and SCA effects for grain yield and other agronomic traits in our study indicated the importance of both additive and non-additive gene effects in the inheritance of these traits [32]. Conversely, the significant GCA but non-significant SCA effects for provitamin A and most carotenoids indicated the predominance of additive gene effects in their inheritance, consistent with the results reported in other studies involving maize inbred lines [26,28,30,49,50]. This, however, contradicts with the results of [27,29] who reported the presence of additive and non-additive gene effects in the inheritance of Provitamin A while [31] reported the preponderance of non-additive gene effects in the inheritance of provitamin A and other carotenoids.…”
Section: Discussionsupporting
confidence: 91%
“…Understanding the effect of marker-based improvement of the two synthetics on their combining abilities for grain yield and other desirable agronomic traits as well as provitamin A carotenoids can provide useful information on the genetic control of these traits and facilitate the identification of suitable source populations for divergent parental lines with good general and specific combining abilities (GCA and SCA) to optimize expression of heterosis in hybrids. Few studies, mainly in maize inbred lines have reported combining ability for grain yield and provitamin A carotenoids [26][27][28][29]. However, the combining ability and heterosis for grain yield, agronomic traits and provitamin A carotenoids in maize synthetics improved using high throughput marker assisted recurrent selection has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most correlation coefficients among lutein, zeaxanthin, β-carotene, lutein+zeaxanthin+βcarotene and total carotenoids at immature stage were positive and significant, ranging from 0.67 to 0.94 at P ≤ 0.01 except for the correlation coefficients between zeaxanthin and lutein and between zeaxanthin and β-carotene. In previous studies in field maize, zeaxanthin was positively and significantly correlated with lutein (Muthusamy et al, 2015;Muthusamy et al, 2016). Different genetic materials might express the different correlations among these traits.…”
Section: Relationship Between Color Parameter and Carotenoidsmentioning
confidence: 78%
“…Cycle 2 had the highest lutein, zeaxanthin, β-carotene, lutein+zeaxanthin+βcarotene and total carotenoids at most locations except for zeaxanthin at Khon Kaen location, in which cycle 1 was highest. The positive responses would be due to sufficient genetic variations in pro-vitamin A, carotenoids (Suwarno et al, 2014;Senete et al, 2011), lutein, zeaxanthin and βcarotene (Muthusamy et al, 2016). Recurrent selection could increase carotenoids in maize (Senete et al, 2011).…”
Section: Recurrent Selectionmentioning
confidence: 99%
“…BC and BCX are the intermediate products of the carotenoid biosynthesis pathway, leading to the more synthesis of final non‐proA products (LUT and ZEA). This is the main reason of maize kernels possessing limited proA, although being abundant in other carotenoids (Muthusamy et al, ). The reduction in non‐proA carotenoids could be the reduction of CRTRB1 transcript acting in carotenoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%